TOURIST POTENTIAL OF AUSTRIA - E. B. Botavina; E. Yu. Churzina (Вестник университета)
An overview of the tourism business in Austria has been presented. The benefits of tourism in Austria have been highlighted. The differences in the tourism business in Austria from other European countries have been given. Statistics on the competitiveness of travel and tourism, the most popular types of entertainment, as well as a comparison of the number of Russians visiting country has been indicated. Prerequisites for further development of high-quality tourism have been considered. Investments in the tourism business have been justified. The role and contribution of the state to the development of tourism in a single country have been analysed. An integrated approach to solving the problems of the tourism business and related fields, including the issues of training specialized personnel has been presented.